The cost-effectiveness of endoscopic treatment and open surgery in the management of vesicoureteral reflux [Vezi̇küreteral reflü tedavi̇si̇nde endoskopi̇k tedav̇i ve açik cerrahi̇ni̇n başari-mali̇yet anal̇iżi] - (:unkn) unknown (My University, 2007)
Introduction: The use of dextronomer/hyaluronic acid particles has become increasingly popular as an alternative to ureteral reimplantation in the management of vesicoureteral reflux. We compared the endoscopic treatment with the open surgery in terms of cost-effectiveness. Materials and Methods: Between 1999 and 2006, a total of 22 children with 31 renal units with vesicoureteral reflux underwent endoscopic treatment with dextronomer/hyaluronic acid particles and 55 children with 91 renal units underwent open surgery were included to the study. These treatment modalities were compared in respect to cost-effectiveness. The total cost of each primary treatment modality has been analyzed per renal unit at the time when reflux was cleared, also including secondary surgery charges. Result: The first and second attempts of infection cleared reflux in 58% and 67% of renal units, respectively. The cost of endoscopic treatment with dextronomer/hyaluronic acid particles was 2,417.7 YTL. Thirteen renal units which failed after initial dextronomer/hyaluronic acid particles injection increased the cost of endoscopic treatment per renal unit up to 2,653.9 YTL. The cost of open surgery per renal unit overall in our study group was 1,496 YTL. This cost per renal unit decreased to 1,286.4 YTL for bilateral ureteral reimplantation with success rate of 100%. Conclusion: Although the current data from western countries have claimed that endoscopic treatment is more cost-effective than open surgery, our results especially in bilateral cases revealed the opposite.
Keywords: Cost; Effectiveness; Treatment; Vesicoureteral reflux